From Engagement to Addiction: Tiktok's impact on Emerging Adults - Gautam, Laxmi; Koirala, Bipana; Adhikari, Pitri Bhakta (Patan Prospective Journal, 2025)
Tiktok, being one of the popular short video platforms has slowly entered in our life as a platform that can be used as a source of entertainment. This study examines the growing influence of Tiktok's algorithm especially on emerging adults and its potential role in mental health issues and addiction. Here secondary data from various reliable sources are used in order to demonstrate the overall growth of Tiktok. Downloads, age demographics, time spent using Tiktok etc are studied and demonstrated. A correlation between Tiktok usage and increased mental health issues is illustrated using graphs and tables. When various data were studied it was found that the emerging adults who are main users of Tiktok are more likely to suffer from mental health issues as compare to other age group. The findings reveal that there is great need of understanding the effect of Tiktok especially on young user's mental health.